Nursing Lecturers’ Transformasional Leadership In Classroom Management At Nursing And Health Faculty Of Muhammadiyah University Of Semarang - Tri Hartiti; Ernawati Ernawati (South East Asia Nursing Research, 2019)
A nursing lecturer is an individual responsible for learning process management of nursing students who are expected to professionally provide health services (care provider) in the forms of biological, psychological, social, and spiritual services to individuals, families, and communities in the future. A nursing lecturer is expected to have competences as a classroom management leader who gives opportunities for students to properly actualize their emotions, the one who effectively utilizes resources, and who does not only focus on the working results (Cummings et al., 2010 and Wong, 2012) known as transformational leadership. Transformational leadership is widely acknowledged as one leadership model which improves human resources. This research aims to figure out the lecturers’ transformational leadership in classroom management at Nursing and Health Faculty of Muhammadiyah University of Semarang. This non experimental (descriptive) research is conducted with a survey approach on a population of 24 nursing lecturers fulfilling inclusion criteria. Result of the reseacrh showed that 79.2% of nursing lecturers are females with an average of 42 years old. 93.9% are master graduates. 54.2% of lecturers have good transformational leadership while the other 45.8% still have poor transformational leadership. 70% of lecturers have charismatic competence while the other 30% have less charismatic competence. 62.5% of lecturers have idealistic persuasive competence while the other 37.5% have less idealistic persuasive competence. 54.2% of lecturers have good inspirational motivation competence while the other 45.8% have less inspirational motivation competence. Most transformational leadership components in classroom management are classified into the good category. However, 45.5 % of them tend to be poor.